Penerapan Qanun Aceh Nomor 14 Tahun 2003 Tentang Khalwat (Mesum) (Studi Kasus Penerapan Syariat Islam di Kota Subulussalam) - Ali Geno Berutu (Jurnal Hukum Islam, 2017)
This paper discusses the implementation of Aceh’s Qanun (the regional law) Number 14 of 2003 on khalwat (mesum/adultery) in Subulussalam city. The current study aims to explain the strategies to deal with the cases of khlawat in Aceh. It was field and library research by carrying out qualitative method and socio-legal-historic approach. The research findings reveal that the cases of khlawat could be solved through the pivotal roles of the local customary court (Mahkamah Adat) and Islamic court (Mahkamah Syar’iyah). The roles arose an uncertainty in handling the cases, particularly for the law enforcement agencies (WH, police officers, prosecutors, and the Mahkamah Syar’iyah). Additionally, the Acehnese Qanun Number 9 of 2008 on the preservation of customary law has explicitly established the problem-solving of lawsuit and its mechanism in an exclusive chapter. The Article 13 Section 1 in this Qanun asserts that the types of lawsuit/dispute of local customs consist of 18 issues. Khalwat is one of the involved issues, and the Mahkamah Adat is the authorized party concerning the issue.